Development of county land use management decision support system - WANG Jian-di; WANG Ren-chao (浙江大学学报. 农业与生命科学版, 2001)
In order to meet the actual demands for managing land resource, a new GIS-based land use management decision support system is explored. This paper introduces county land use management decision support system (CLUMDSS) which we have developed. CLUMDSS consists of spatial database, attribute database, Mathematical models and land use analytical subsystem and human-computer interactive interface. A full consideration of national gap and users' actual needs was given in the present CLUMDSS exploration. Pilot experiments in Ruian City of Zhejiang Province demonstrated that CLUMDSS was able to meet the needs of land management institutions at county. There exists prosperous future for popularizing and utilizing CLUMDSS throughout the country.